Profile of Frailty and the occurrence of falls in older adults - Souza, Ana Claudia de; Siqueira, Maria Eliane Catunda de; McNulty, Craig; Neri, Anita Liberalesso (Revista Kairós-Gerontologia, 2021)
The study aimed to analyze the prevalence of frailty syndrome and correlate with the occurrence of falls, in a sub-sample of Rede Fibra, composed of 318 older adults aged 65 and over. It was found a high prevalence of pre-frail older adults and a high incidence of falls among them. However, there was no statistically significant difference. Further studies are needed to identify the frailty syndrome and to present an intervention to prevent and rehabilitate adverse effects such as falls.